2005
DOI: 10.1111/j.1540-8159.2005.09518.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygenation During Defibrillator Threshold Testing of Implantable Cardioverter Defibrillators

Abstract: Our results suggest that impaired oxygen delivery during induced VF and VT does not affect oxygen availability at the cellular intra-mitochondrial level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The NIRO 300 instrument has overall been shown to produce valid measurements of the oxCCO signal. 20,[45][46][47][48][49][50][51][52][53] However, it belongs to those early-generation instruments that used only four discrete wavelengths (775, 810, 850, and 910 nm, respectively) to assess both the metabolic and hemodynamic signals. These wavelengths are in relatively good agreement with the optimal wavelengths reported for CCO measures.…”
Section: Discussionmentioning
confidence: 99%
“…The NIRO 300 instrument has overall been shown to produce valid measurements of the oxCCO signal. 20,[45][46][47][48][49][50][51][52][53] However, it belongs to those early-generation instruments that used only four discrete wavelengths (775, 810, 850, and 910 nm, respectively) to assess both the metabolic and hemodynamic signals. These wavelengths are in relatively good agreement with the optimal wavelengths reported for CCO measures.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Moderate ⊕⊕⊕◯ Critical False negative Moderate ⊕⊕⊕◯ Important POCUS cardiac motion assessment False positive 0 g (0) NA (no studies used IAP monitoring as reference test) No direct evidence or comparison with invasive arterial blood pressure monitoring. Very low ⊕◯◯◯ Critical False negative Very low ⊕◯◯◯ Important NIRS False positive 3 g (30) 1 case series 23 2 prospective cohort 27 , 28 No rSO 2 threshold has been suggested in the literature. Two studies have shown correlation between rSO 2 and perfusion 23 , 27 In one observational study ( n = 6), the absolute rSO2 value at the moment death had a broad range.…”
Section: Resultsmentioning
confidence: 99%
“… 23 Indirect evidence is from one reported case ( n = 1, Slavin et al . ), 24 two case-control studies, 25 , 26 two observational studies during defibrillator implantation, 27 , 28 and one pediatric study. 29 No measures of diagnostic accuracy were reported and no threshold for NIRS was suggested.…”
Section: Resultsmentioning
confidence: 99%
“…There was only one report of using NIRS to study cytochrome c oxidase in humans. It showed that there were no significant changes in redox status during the brief period of ischemia that occurs during surgical cardiac defibrillator replacement [35]. Two swine studies sought to gain insight into the differences in cytochrome redox status results seen between previous investigators.…”
Section: Recent Advancesmentioning
confidence: 99%